1933. Economic Evaluation of Outpatient Parenteral Antimicrobial Therapy in Children. (26th November 2018) - Krah, Nathan; Esquibel, Lawanda; Bardsley, Tyler; Nelson, Richard E; Pavia, Andrew; Hersh, Adam L
Abstract: Background: Outpatient parenteral antimicrobial therapy (OPAT) is a safe and effective method to treat serious infections in the home environment. Compared with prolonged hospitalization, OPAT has lower costs and burden on patients and caregivers. However, there is increasing evidence that outcomes with oral therapy are comparable to OPAT in some conditions. Our objective was to compare the economic burden between OPAT and oral therapy. Methods: Prospective cohort study of caregivers for children hospitalized at Primary Children's Hospital, a 289-bed freestanding children's hospital. At an initial visit to the Pediatric Infectious Diseases clinic after hospitalization, subjects completed an electronic survey that included caregiver and medical record components. The caregiver component collected data about missed school, work, comfort with medication administration (5-point Likert scale) and time spent administering therapy. Caregivers also completed the PedsQL, a validated instrument to assess caregiver quality-of-life (QoL). Scores range from 0 to 100 with higher scores indicating better functioning. The medical record component collected clinical information including length of stay and type of therapy (OPAT vs. oral). Direct medical costs were obtained using the Intermountain Healthcare microcosting system and accounted for medication, supplies and home nursing visits. The primary cost outcome was the mean daily cost of therapy. Multivariable models were developed to adjust for potential confounders. Results: Two hundred twelve caregivers completed surveys: 123 (58%) oral and 89 (42%) OPAT (table). Caregivers administering OPAT reported missing more work and the child missing more school, lower levels of comfort with medications (2.09 vs. 2.87, P < 0.01), more time with daily administration (90 minutes vs. 6 minutes, P < 0.01) and lower QoL scores (77.8 vs. 68.9) than caregivers administering oral therapy. Mean daily costs were $65 (95% CI: $51–$78) for OPAT and $7 (95% CI: $4–$9) for oral. The relative differences in cost and QoL between groups did not change after model adjustment. Conclusion: The overall burden of OPAT is substantially higher than oral therapy including higher direct and indirect costs and greater impact on caregiver and patient QoL. Disclosures: All authors: No reported disclosures.